CARBON TAX AND ITS EFFECT ON THE ECONOMY, TAXES AND ENVIRONMENT - Emelia Retno Kadarukmi, Maria (Awang Long Law Review, 2023)
This research discusses theoretically the relationship between carbon tax with economy, tax and environment. This research is a legal research with analytical descriptive nature, namely research that analyzes secondary data on issues related to carbon taxes as an instrument for reducing carbon dioxide emissions. According to secondary data, this research is aimed at discovering aspects of carbon tax design, collection of carbon taxes, and state management of carbon tax revenues. Carbon taxes are an effective and efficient instrument to support the reduction of carbon dioxide emissions. To be implemented, a carbon tax must be feasible. Eligibility requires public acceptance. On the other hand, a carbon tax can create a lot of controversy. The main argument against carbon taxes is that carbon taxes do not always guarantee emission reductions. In addition, there are also concerns over the unintended effects of competitiveness, carbon leakage, and fears of unintended distributional impacts, which could be barriers to implementation.